Long-term survival after Acute Ischemic Stroke by types of reperfusion therapy, sex and chronic treatments of cardiovascular conditions - José Luis Clua-Espuny; Sònia Abilleira; Queralt-Tomas M Lluïsa; González-Henares MA; Muria-Subirats E; Ballesta-Ors J; Gil-Guillen V Fco (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2018)
Purpose: Compare long-term survival by sex after reperfusion therapies with simultaneous medical therapy of cardiovascular conditions.  Methods: AIS patients identified from the population-based register between 01Jan2011 and 31Dec2012 and classified into: 1) AIS + intravenous thrombolysis [group I], 2) AIS + mechanical thrombectomy with or without intravenous thrombolysis [group II], and 3) AIS + medical therapy alone (no reperfusion therapies) [group III]. Follow-up went through up until December 2016. Statistical approaches were employed for analyzing survival outcomes and their relationship with reperfusion therapy.  Results: 14,368 AIS patients (men 50.1%), 77.1±11.0 years-old. There was higher survival among those treated with intravenous thrombolysis (p <0.001); women treated with thrombectomy (p <0.001); and women <80 year-old without reperfusion therapy. The most common medications were antiplatelets (52.8%), associated with lower survival (p<0.001); and statins (46.5%), associated with higher survival. The regression model produced the following independent outcome variables associated to mortality: anticoagulant HR 1.53 (CI95% 1.44-1.63, p<0.001), diuretics HR 1.71 (CI95% 1.63-1.79, p<0.001), antiplatelet HR 1.49 (CI95% 1.42-1.56, p<0.001), statins HR 0.73 (CI95% 0.70-0.77, p<0.001), A-IIRA HR 0.93 (CI95% 0.89-0.98, p=0.008) and reperfusion therapy HR 0.88 (CI95% 0.81-0.97, p=0.009).  Conclusions: Under 80 year-old the women had a better outcome than men when treated with thrombolysis therapy and/or catheter-based thrombectomy and with medical therapy alone. The men had a better outcome when received intravenous thrombolysis. The chronic cardiovascular pharmacotherapy must be evaluated to determine their effects on the reperfusion therapy outcome and whether they should be included as factors in the decision to reperfusion. Long-term survival after Acute Ischemic Stroke by types of reperfusion therapy, sex and chronic treatments of cardiovascular conditions.  Long-term Survival differences after reperfusion therapy.